PENAL AND NON-PENAL POLICIES AGAINST THE CRIME OF THEFT WITH VIOLENCE (STUDY AT THE BELAWAN PORT POLICE) - Asun Nelson Junedy Simanjuntak; M. Citra Ramadhan; Serimin Pinem (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research is entitled Non-Penal Policy Against Violent Theft (Study at Belawan Police). The formulation of the problem is (1) What are the factors that cause perpetrators to commit violent theft? (2) How is the non-penal policy made by Belawan Police in overcoming violent theft? (3) What are the obstacles faced by Belawan Police in implementing non-penal policies for perpetrators of violent theft? The research method used is normative legal research, with a descriptive analysis research type. The problem approach uses a normative legal approach. The data used are primary and secondary data. The results of the study show that (1) the factors that cause perpetrators to commit violent theft are economic factors, low education factors, unemployed factors, victim negligence factors, social factors, and lifestyle factors. (2) The non-penal policy made by Belawan Police is a preventive policy, namely by always conducting routine raids in areas prone to violent theft. And a repressive policy, namely by enforcing the law in accordance with statutory regulations. (3) The obstacles faced by the Belawan Police in implementing non-penal policies are obstacles from victims who died, children who are still minors, perpetrators who fled, and limited human resources at the Belawan Police. The suggestion from this thesis is for parents to always look after and educate their children in religious values so that they do not get involved in committing violent theft.